(untitled) (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2017)
This study aims to improve student learning outcomes on Social Problem material by using the method of Role Playing class IV SD Negeri 101768 Tembung. This research use design of PTK with Subject in this research is all side of class IV SDN 101768 Tembung Year Ajisi 2016/2017 which amounts 23 people. This research was conducted two cycles, namely cycle I and cycle II. Setiaap Cycle consists of 4 stages of planning, action implementation, observation and reflection. Data collection techniques used are tests and observations. Problem given 3 times the initial test, cycle I, cycle II, while the observation includes the activities of teachers and students in the learning process. Where the value of learning completeness standard is 65. If the student score is less than 65, then the student is said not yet completed. At the time of Cycle I can be seen that of 23 students of students as many as 9 students (39.13%) who got the results of learning is not complete and as many as 14 students (60.87%) who entered in the category of complete with average class of 63.48. When compared with the initial test score, then there has been an increase in student learning outcomes. Based on the Cycle II test, 2 students (8.70%) were unfinished in the study and as many as 21 students (91.30%) completed in the study with grade point average of 79.57. After the learning and test in Cycle II, the students’ learning outcomes in the IPS lesson and the next cycle are no longer necessary. Based on the results of the study can be concluded that. Implementation of role playing method to improve student learning outcomes in social studies subjects in class IV SD Negeri 101768 Tembung T.A 2016/2017.